ANALISIS KONTRASTIF PENGGUNAAN PRONOMINA PERSONA KEDUA ANATA DALAM BAHASA JEPANG DENGAN ANDA DALAM BAHASA INDONESIA - Revian Novaldiansyah Gumilar, - (2023)
Everyone uses language as a tool to convey an idea, thought, and purpose to others. In Japanese, there is a level of speech known as keigo, which is divided into 3 namely sonkeigo, kenjougou, and teineigo. The second person pronoun anata belongs to the sonkeigo level which means directly you in Indonesian. The use of keigo is arbitrary because it can lead to different meanings. In Indonesian, there is a possibility that anda personal pronoun will have similarities with the anata personal pronoun which attracts the author's attention. This study aims to find the similarities and differences between the personal pronoun anata and you both in terms of usage and function. The method used is descriptive qualitative. The researcher took data from published works randomly. The data obtained amounted to 50 sentences divided into 25 data on the use of personal pronoun anata and 25 data on the use of your personal pronoun. Based on the analysis of the personal pronoun anata and anda have similarities including can be used by anyone, function, use, social relationship factors, age factors, purpose factors. While the differences include: changes in meaning, familiarity factor, group membership factor, and situation factor.